Desire, Mimesis, and the Phylogeny of Freedom - Hurlbut, William B. (Mimesis and science, 2011)
Desire and its disordered dynamics is the central theme of Ren Girard?s theory of mimetic process and its role in the foundations of human culture. Indeed, the early insights that led to mimetic theory were drawn from literary portraits revealing the unique character of human desire, its indeterminate nature, and its elaboration through imitation. These insights have been reaffirmed and extended through their application to anthropology, sociology, and economic theory, and, in turn, have greatly illuminated these fields of study. Now, with the new tools of social cognitive neuroscience, we may further expand our understanding of sociality, desire, and mimetic